2021
DOI: 10.1038/s41598-020-79359-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic adaptation of Pseudomonas strains to acidity and antibiotics in hydrothermal vents at Kolumbo submarine volcano, Greece

Abstract: Although the rise of antibiotic and multidrug resistant bacteria is one of the biggest current threats to human health, our understanding of the mechanisms involved in antibiotic resistance selection remains scarce. We performed whole genome sequencing of 21 Pseudomonas strains, previously isolated from an active submarine volcano of Greece, the Kolumbo volcano. Our goal was to identify the genetic basis of the enhanced co-tolerance to antibiotics and acidity of these Pseudomonas strains. Pangenome analysis id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…Until the SANTORY observatory, sampling for microbial diversity was performed sporadically. Despite the vital role of microorganisms in hydrothermal vent ecosystems, only recently have bio-geochemical (Kilias et al, 2013;Christakis et al, 2018) and metagenomics and genomic investigations (Oulas et al, 2016;Mandalakis et al, 2019;Bravakos et al, 2021) been performed at Kolumbo volcano. These investigations revealed that both Kolumbo crater and Santorini caldera harbor highly complex prokaryotic communities (Oulas et al, 2016;Christakis et al, 2018) and microbes with an enhanced co-tolerance to acidity and antibiotics (Mandalakis et al, 2019;Bravakos et al, 2021).…”
Section: Expected Results-discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Until the SANTORY observatory, sampling for microbial diversity was performed sporadically. Despite the vital role of microorganisms in hydrothermal vent ecosystems, only recently have bio-geochemical (Kilias et al, 2013;Christakis et al, 2018) and metagenomics and genomic investigations (Oulas et al, 2016;Mandalakis et al, 2019;Bravakos et al, 2021) been performed at Kolumbo volcano. These investigations revealed that both Kolumbo crater and Santorini caldera harbor highly complex prokaryotic communities (Oulas et al, 2016;Christakis et al, 2018) and microbes with an enhanced co-tolerance to acidity and antibiotics (Mandalakis et al, 2019;Bravakos et al, 2021).…”
Section: Expected Results-discussionmentioning
confidence: 99%
“…Despite the vital role of microorganisms in hydrothermal vent ecosystems, only recently have bio-geochemical (Kilias et al, 2013;Christakis et al, 2018) and metagenomics and genomic investigations (Oulas et al, 2016;Mandalakis et al, 2019;Bravakos et al, 2021) been performed at Kolumbo volcano. These investigations revealed that both Kolumbo crater and Santorini caldera harbor highly complex prokaryotic communities (Oulas et al, 2016;Christakis et al, 2018) and microbes with an enhanced co-tolerance to acidity and antibiotics (Mandalakis et al, 2019;Bravakos et al, 2021). The observatory will enable microbiologists to locate and revisit specific microbiological features of the vent field, to study the microbial communities' composition, structure and response to changes in the volcanic/hydrothermal system and to understand the physicochemical factors that shape the antibiotic resistome.…”
Section: Expected Results-discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, microorganisms living in hydrothermal vents may tend to enrich various stress tolerance genes via HGT, which could be helpful for them to adapt to harsh environmental conditions (e.g., high temperatures and toxic gases) [33]. It has been suggested that ARGs are beneficial for thermal microorganisms not only in terms of coping with selective environmental stresses [34], but also for competing with other species [35]. Some prior investigations have shown that ARGs were ubiquitous in diverse pristine environments, including plateau lake sediments [36], polar soils [37], hot springs [38,39] and deep-sea hydrothermal vents [35]; however, it is difficult to compare the results of different studies as different methodologies were used for ARG analysis in different studies.…”
Section: Introductionmentioning
confidence: 99%